2002
DOI: 10.1159/000065056
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Capsaicin Receptors on the Sciatic Nerve Induces FOS Expression in the Spinal Dorsal Horn of Adult Rats

Abstract: By using immunohistochemical staining for FOS protein in the spinal cord, the role of capsaicin receptors on the sciatic nerve was investigated. After topical application of capsaicin (1%) to the sciatic nerve, FOS-like immunoreactive (FOS-LI) neurons were observed, chiefly in the superficial laminae of the lumbar dorsal horn. Topical application of capsazepine (5%) or lidocaine (2%) to the sciatic nerve for 15 min before the application of capsaicin reduced the number of FOS-LI neurons in the superficial dors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Previous studies reported that injury discharges were accompanied by increased expression of c-Fos LI cells in the spinal cord dorsal horn (Feng et al, 2002;Sun et al, 2004;Stenberg et al, 2005), while lidocaine pre-treatment could inhibit injury discharges and significantly reduce expression of c-Fos-LI cells in the spinal cord dorsal horn at 2 days after injury (Chi et al, 1993;Sun et al, 2004). Interestingly, the lidocaine-induced reduction in the rate of injury discharges and the number of NPY-LI fibers and c-Fos-LI cells in the present study were maintained up for 4 weeks after MNT, while the expression of c-Fos-LI cells in the CN was correlated with the level of NPY reduction.…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies reported that injury discharges were accompanied by increased expression of c-Fos LI cells in the spinal cord dorsal horn (Feng et al, 2002;Sun et al, 2004;Stenberg et al, 2005), while lidocaine pre-treatment could inhibit injury discharges and significantly reduce expression of c-Fos-LI cells in the spinal cord dorsal horn at 2 days after injury (Chi et al, 1993;Sun et al, 2004). Interestingly, the lidocaine-induced reduction in the rate of injury discharges and the number of NPY-LI fibers and c-Fos-LI cells in the present study were maintained up for 4 weeks after MNT, while the expression of c-Fos-LI cells in the CN was correlated with the level of NPY reduction.…”
Section: Discussionmentioning
confidence: 94%
“…Fos protein is rapidly expressed in the spinal dorsal horn neurons following noxious peripheral nerve stimulation [21] and correlates well with nociceptive behaviors [19]. Thus, Fos expression is used to identify nociceptive input activated or excited population of neurons [22], [23], [24].…”
Section: Introductionmentioning
confidence: 99%
“…This study further showed that the number of c-Fos-LI cells was dose-dependently reduced by lidocaine pre-treatment. Injury discharges have been reported to be implicated in the increase of c-Fos LI cell expression in the spinal cord dorsal horn [3234], while lidocaine pre-treatment attenuates the discharges to prevent c-Fos induction [21, 34]. …”
Section: Discussionmentioning
confidence: 99%